A PadR family transcriptional repressor controls transcription of a trivalent metalloid resistance operon of Azospirillum halopraeferens strain Au 4 - Zhang, Jun; Wu, Yi‐Fei; Tang, Shi‐Tong; Chen, Jian; Rosen, Barry P.; Zhao, Fang‐Jie (Environmental microbiology, 2022)
Methylarsenite [MAs(III)] is a highly toxic arsenical produced by some microbes as an antibiotic. In this study, we demonstrate that a PadR family transcriptional regulator, PadRars, from Azospirillum halopraeferens strain Au 4 directly binds to the promoter region of the arsenic resistance (ars) operon (consisting of padRars, arsV, and arsW) and represses transcription of arsV and arsW genes involved in MAs(III) resistance. Quantitative reverse transcriptase PCR and transcriptional reporter assays showed that transcription of the ars operon is induced strongly by MAs(III) and less strongly by arsenite and antimonite. Electrophoretic mobility shift assays with recombinant PadRars showed that it represses transcription of the ars operon by binding to two inverted‐repeat sequences within the ars promoter. PadRars has two conserved cysteine pairs, Cys56/57 and Cys133/134; mutation of the first pair to serine abolished the transcriptional response of the ars operon to trivalent metalloids, suggesting that Cys56/57 form a binding site for trivalent metalloids. Either C133S or C134S derivative responses to MAs(III) but not As(III) or Sb(III), suggesting that it is a third ligand to trivalent metalloids. PadRars represents a new type of repressor proteins regulating transcription of an ars operon involved in the resistance to trivalent metalloids, especially MAs(III).